what is Academic advising - SAKHRI, Mohamed; BENKOUIDER, Mayada (Social Sciences Journal, 2021)
This paper aims to highlight on what academic advising is which is considered as a process that leads to achieving a healthy, integrated growth of the learner’s personality and achieving psychological and academic harmony. The latter works to help the university student to move quietly from one stage to another by developing self-motivation for study, comprehension ability and definition on how to set academic goals that can be achieved. And since university students are the builders of the future, they must be accompanied by academic guidance, which is the primary activity that accompanies the university student from the beginning of his choice of specialization until he reaches the highest level of science. so, looking at academic counseling as an indispensable human experience and educational skill in light of these stressful events and external influences that have produced many psychological and educational problems the existence of an educational psychological counseling intervention to immunize the younger generations against these difficulties and dangers is required.